1993
DOI: 10.1111/j.1440-1746.1993.tb01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive‐somatostatin concentrations of the human stomach and mood state in patients with functional dyspepsia: A preliminary case–control study

Abstract: Immunoreactive-somatostatin (ir-SS) concentrations of the gastric mucosa and mood state in patients with functional dyspepsia were examined. The subjects were 12 patients with upper abdominal discomfort, nausea and/or vomiting (motility disorder group) and 14 patients complaining of upper abdominal pain (ulcer-like disorder group) for more than a month without any organic upper-gastrointestinal tract disease proven by endoscopy. These patients were compared with either an age- and sex-matched group of asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Despite substantial differences in experimental design, the relations found in this study between type of distress and type of FGID support previous associations (for example, depression with DL dyspepsia27; hypochondriasis with IBS28-30; and emotional distress (anxiety and depression) with heartburn/reflux31). The present findings, however, shed further light on how personality, chronic social stressors, and distress may differentially influence the development and/or exacerbation of FGID.…”
Section: Discussionsupporting
confidence: 85%
“…Despite substantial differences in experimental design, the relations found in this study between type of distress and type of FGID support previous associations (for example, depression with DL dyspepsia27; hypochondriasis with IBS28-30; and emotional distress (anxiety and depression) with heartburn/reflux31). The present findings, however, shed further light on how personality, chronic social stressors, and distress may differentially influence the development and/or exacerbation of FGID.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, 6 months after H. pylori eradication, approximately 27 % of the treated FD patients had a recurrence [79]. Some previous studies have suggested that psychological problems are more commonly seen in FD patients than in patients with peptic ulcer disease and healthy controls [80,81], but another study indicates that psychological problems in FD patients occurred at the same frequency as in healthy individuals [82]. A meta-analysis based on studies that were performed up to 2001 suggested that there was no significant difference in the ratios of affective disorders and neurotic disorders between FD patients and healthy individuals [23].…”
Section: Prognosis and Complicationsmentioning
confidence: 88%
“…Recently, it has been suggested that exposure of the esophagus and duodenum to gastric acid is also a cause of dyspepsia symptoms . Furthermore, several common pathophysiological features such as hyperesthesia and abnormal motor function, as well as psychological factors, are observed with both conditions . Nevertheless, there is ongoing discussion concerning the differences between these two diseases .…”
Section: Discussionmentioning
confidence: 99%
“…4,14-16 Furthermore, several common pathophysiological features such as hyperesthesia and abnormal motor function, as well as psychological factors, are observed with both conditions. [17][18][19][20][21][22][23][24][25] Nevertheless, there is ongoing discussion concerning the differences between these two diseases. 6,7 To investigate this issue, we compared demographics and treatment response to the proton pump inhibitor lansoprazole between patients with FD and patients with NERD.…”
Section: Discussionmentioning
confidence: 99%